Asymmetric Fitness of Second-Generation Interspecific Hybrids Between Ciona robusta and Ciona intestinalis - Ohta, Naoyuki (G3 (Bethesda), 2020)
Reproductive isolation is central to speciation, but interspecific crosses between two closely related species can produce viable and fertile hybrids. Two different species of tunicates in the same ascidian genus, Ciona robusta and Ciona intestinalis, can produce hybrids. However, wild sympatric populations display limited gene flow, suggesting the existence of obstacles to interspecific reproduction that remain unknown. Here, we took advantage of a closed culture system to cross C. robusta with C. intestinalis and established F1 and F2 hybrids. We monitored post-embryonic development, survival, and sexual maturation to characterize the genetic basis of simple traits, and further probe the physiological mechanisms underlying reproductive isolation. Partial viability of first and second generation hybrids suggested that both pre- and postzygotic mechanisms contributed to genomic incompatibilities in hybrids. We observed asymmetric fitness, whereby the C. intestinalis maternal lines fared more poorly in our system, pointing to maternal origins of species-specific sensitivity. We discuss the possibility that asymmetrical second generation inviability and infertility emerge from interspecific incompatibilities between the nuclear and mitochondrial genomes, or other maternal effect genes. This work paves the way to quantitative genetic approaches to study the mechanisms underlying genomic incompatibilities and other complex traits in the genome-enabled Ciona model.